G257(P) The ethics of therapy pets on paediatric wards: a rabbit case study. (May 2019) - Machta, JS; Fertleman, C
Abstract : Aims: The use of animals as therapeutic aids in physical and mental illness is a well established trend, with multiple hospitals throughout the UK hosting therapy animals during short day visits. There is a paucity of discussion on the ethics of keeping animals on hospital wards permanently. Methods: The ethical benefits and problems of keeping an in-hospital pet permanently (using a known case, a Rabbit on a Paediatric ward) were explored and scrutinised against the four pillars of medical ethics: beneficence, non-maleficence, autonomy, and justice. Effects on the animal itself, patients, and staff were considered. Results: Benificence: the Rabbit benefitted greatly from being adopted by our ward, as she was due to no longer have a home with humans beforehand. Furthermore, we have performed extensive survey studies demonstrating significantly increased feelings of patient wellbeing and staff satisfaction due to the presence of the Rabbit. Non-maleficence: care must be taken to reduce the risk of harm to the Rabbit through careful handling, regular feeding, and cleaning. The risk of doing harm to staff and patients has been shown to be minimal, except for isolated incidences of mild allergic reactions and light scratching. Autonomy: the nature of the master-pet, or companion-companion relationship between the ward team and the Rabbit naturally lends itself to removal of autonomy from the Rabbit, as she is dependent on humans for food, shelter, and maintaining basic hygiene. Justice: all individuals handling the Rabbit are treated equally, and all patients given equal time with her. Conclusion: The advantages of keeping a paediatric ward pet in the form of a Rabbit have been shown to outweigh the disadvantages, and so we advise this innovation as a beneficial one.